Immunohistochemical analysis of soft tissue response to polyetheretherketone (PEEK) and titanium healing abutments on dental implants: a randomized pilot clinical study - Iva Milinkovic; Ana Djinic Krasavcevic; Sasha Jankovic; Jelena Sopta; Zoran Aleksic (BMC, 2022)
Abstract Background The data on polyetheretherketone (PEEK) influence on the peri-implant soft tissues in clinical settings are deficient. The aims of this pilot study were to analyze and compare soft tissues' response to PEEK and titanium (Ti) healing abutments (HA) by means of histological and immunohistochemical analyses. Methods A total of 22 implants with PEEK or Ti HA were placed in 11 patients, applying the "split-mouth" study design. Three months later, soft tissue specimens were harvested from 20 implants for histology in order to qualitatively detect the inflammatory cells' presence, to semi-qualitatively analyze the inflammation intensity and to assess the inflammatory responses type by immunohistochemical analysis using LCA, CD3, CD20 and CD68 antibodies. Results Epithelial infiltrate followed by an intensive inflammation in sub-epithelium was observed in 100% around PEEK HA. A number of LCA+ and CD 68+ cells was significantly higher in PEEK comparing to Ti group (p = 0.001 and p = 0.020, respectively), while CD 20+ and CD3+ counted cells were found in a significantly higher amount in Ti than in PEEK group (p = 0.006 and p = 0.010, respectively). Conclusion PEEK HA seems to evoke the more intense tissue inflammatory response demonstrated predominantly by histocytes' and plasmacytes' activation, while Ti HA triggers the inflammatory reaction of lower intensity, dominantly mediated by B-cells. Trial registration The study registered at ClinicalTrials.gov (NCT04436939).